O despertar de Cthulhu na cibercultura: as ressignificações do personagem de H. P. Lovecraft realizadas por fãs no facebook - Kurtz, Gabriela Birnfeld (2015)
The present work has as objective to comprehend fans appropriations and reframing (Jenkins, Hills, Jenson) of the character Cthulhu, Howard Phillips Lovecraft s creation, in the context of cyberculture (Lévy, Manovich, Castells, Santaella). Lovecraft, born in Providence, United States, lived between 1890 and 1937, and wrote short stories and poems on the fantastic genre of literature. His creations survived time, being modified and reinterpreted in different entertainment spheres and, in cyberculture, appropriated by fans in large scale around the world. By the analysis of posts and conversations in the page Cthulhu , on Facebook, it was objectified to comprehend who is the fans Cthulhu. In addition, it was aimed to investigate what would the differences be between these reframings and Lovecraft s short story, The Call of Cthulhu , in a context where the new media and the Social Network Websites amplify and facilitate content s production methods and its propagation among the fandom. The methodologies chosen were the documental analysis and the conversation analysis in social media, being done together and later on related with the theoretical approaches chosen. Through the research, the character, before a terrible and irrational monster, gained from the fans personality, human traits, merged with memes and transcended its purpose beyond the original short story destroying humanity -, becoming a socializing creature.